2022
DOI: 10.1021/acsami.2c12823
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Construction of an Enzyme-Mimetic Supramolecular Nanoagent for RNS-Augmented Cascade Chemodynamic Therapy

Abstract: Inspired by natural enzymes, specific enzyme-like cascade catalytic reactions can be obtained by imitating the metal active sites of natural enzymes and assembling inorganic materials at the molecular level via supramolecular interactions, which can greatly expand their application in biology. Herein, it is reported that a bioinspired SNP/MgMnFe-LDH (denoted as S2MFL) supramolecular nanoagent has been successfully synthesized via the intercalation between nitroprusside (SNP) and MgMnFe-layered double hydroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Additionally, SNP anion ([Fe-CN) 5 NO ]2- ), as a GSH-responsive NO donor, can release NO upon activation of GSH in tumor cells. Zhou et al successfully synthesized SNP/MgMnFe-LDH (S2MFL) supramolecular nano-reagent containing both Mn 2+ and SNP anions, and the synergistic effect of Mn 2+ and SNP can produce high levels of ONOO - to cause DNA fragmentation for synergistic CDT/NO anti-tumor 188 .…”
Section: Cdt-based Combination Therapymentioning
confidence: 99%
“…Additionally, SNP anion ([Fe-CN) 5 NO ]2- ), as a GSH-responsive NO donor, can release NO upon activation of GSH in tumor cells. Zhou et al successfully synthesized SNP/MgMnFe-LDH (S2MFL) supramolecular nano-reagent containing both Mn 2+ and SNP anions, and the synergistic effect of Mn 2+ and SNP can produce high levels of ONOO - to cause DNA fragmentation for synergistic CDT/NO anti-tumor 188 .…”
Section: Cdt-based Combination Therapymentioning
confidence: 99%
“…[18]. Therefore, to improve the properties of SNP, researchers are designing and developing various SNP based nanomaterials by introducing metals in SNP complex or by incorporation of SNP in different nanomaterials for better therapeutic efficacy in order to overcome the complications and health consequences associated with the use of bare SNP [10,11,13,14,34,35]. These metal nitroprusside nano analogues possesses versatile physiochemical properties such as electrochemical, photocatalytic, photodegradation and sensing properties [36].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the exogenous supplementation of SOD to remove excessive ROS and relieve chronic pain is a promising strategy. [ 8 ] Nevertheless, this strategy faces two dilemmas: 1) in vivo stable delivery of SOD molecules with resolved enzyme activity should be addressed; 2) synergistic enzyme catalysis should be designed to convert the produced H 2 O 2 catalyzed by SOD enzyme into lower oxidation O 2 for maximal ROS elimination. [ 9 ] Recently, increasing evidence has shown that inorganic antioxidant enzyme nanoparticles (NPs) can treat multiple diseases and show better stability and efficacy than natural enzymes.…”
Section: Introductionmentioning
confidence: 99%